Pengaruh Teknik Keterampilan Long Service Bulu Tangkis dengan Metode Service Challenge Drill pada Atlet PB. Mezaluna Kebumen Usia 9 – 12 Tahun : Penelitian - Mokhamad Parmadi; Agus Hendrianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Long badminton service can press the opponent's position to the back line so as to create space in front of the court for attack. The purpose of this study was to determine the level of long service ability of PB Mezaluna Kebumen badminton players aged 9-12 years before and after being introduced to the service challenge drill method. The population in the study were members of the PB Mezaluna Kebumen school consisting of 50 people. While the sample in this study was those who met the criteria, namely 15 people with details of 10 boys and 5 girls. Sampling by considering the activeness of participating in PB Mezaluna Kebumen training, willing to follow the treatment, and aged 9-12 years. The instrument used in this study was a Long Service Technique test instrument of 20 service strokes before the sample was given treatment, and posttest data of 20 service strokes after the sample was given Long Service treatment. The results of the study showed the accuracy of the increase in service strokes as seen from the results of the initial test (pretest) with an average value of 21.07 and the final test (posttest) of 29.67. So that there was an increase of 8.6 with a percentage increase of 40.81%, the results of the study sig. (0.000) <0.05 so that there is a positive and significant influence of the service challenge drill method on the ability of long service strokes, the use of the service challenge drill method can improve the ability and accuracy of long service strokes.